Hubungan Riwayat Anemia saat Kehamilan dengan Kejadian Anemia Postpartum pada Ibu Nifas - Endang Yuliani (EMBRIO: Jurnal Kebidanan, 2020)
Anemia during pregnancy has become a national problem and has a major impact in the postpartum period, so it requires the attention of all parties related to health problems. This type of research uses observational analytic where the research design uses the cross sectional method with a sample of 10 respondents in this study taken by nonprobability sampling with accidental sampling type. Data were analyzed using Spearman rho test. The results of the Spearman rho test obtained a significant value of 0.000 <0.05, so it can be concluded that there is a relationship between a history of anemia during pregnancy and the incidence of postpartum anemia in postpartum mothers at the Kejayan Public Health Center, Pasuruan Regency in 2020